Total synthesis of four stereoisomers of (5Z, 8Z, 10E, 14Z)-12-hydroxy-17, 18-epoxy-5, 8, 10, 14-eicosatetraenoic acid and their anti-inflammatory activities. Issue 43 (28th October 2015) - Goto, Tomomi; Urabe, Daisuke; Isobe, Yosuke; Arita, Makoto; Inoue, Masayuki
Abstract: The four stereoisomers of novel lipid mediator 1, (5 Z, 8 Z, 10 E, 14 Z )-12-hydroxy-17, 18-epoxy-5, 8, 10, 14-eicosatetraenoic acid, were synthesized from six simple fragments. Triyne 2 was convergently assembled through three SN 2 alkynylation reactions and one Sonogashira coupling reaction. Two of the three alkynes of 2 were hydrogenated using Lindlar catalyst, while the third alkyne was reduced through formation of the alkyne-dicobalt hexacarbonyl complex and subsequent reductive decomplexation, producing the requisite tetraene structure in a stereoselective manner. Next, a two-step functional group manipulation at C1, followed by simultaneous deprotection and epoxide formation, gave rise to the four isomers, (12 S, 17 R, 18 S )-1aa, (12 S, 17 S, 18 R )-1ab, (12 R, 17 R, 18 S )-1ba and (12 R, 17 S, 18 R )-1bb . The present work allowed determination of the absolute structure of naturally occurring 1 to be 1aa and 1ab, as well as biological evaluation of the two natural (1aa, 1ab ) and two unnatural (1ba, 1bb ) isomers. Intriguingly, natural 1aa and unnatural 1ba were found to exhibit more potent anti -inflammatory activities than 1ab and 1bb, indicating the greater importance of the stereochemistry of the C17, 18-epoxide compared to that of the C12-hydroxy group. Graphical abstract: